Students' Perceptions on Collaborative Learning in Teaching Speaking by Using Blended Learning - Fathana, Siti; Fajri, Dede Rohadi; Qonaatun, Aa (FKIP, Universitas Banten Jaya, 2024)
The objective of this research was to find out how students perceive English learning using the blended learning method combined with a collaborative learning approach and to find out what advantages teachers and students get when learning using collaborative learning. The research is a qualitative case study, and the data was collected by observations and interviews with students and teachers. The results of this research indicate that almost all students agree that collaborative learning can help them to improve their skills in English subjects. In addition, from the results of observations, students are more active in collaborative learning. By applying collaborative learning, students can discuss problem-solving and have more opportunities to practice speaking. Collaborative learning using blended learning is a new learning approach that can improve students' ability, in conclusion the writers hope this finding can help students increase their confidence in learning speaking. The writers realize that this research is not perfect, but the writers hope that this research can inspire English teachers and future researchers.